Dialog Pemikiran Tentang Norma Riba, Bunga Bank, Dan Bagi Hasil di Kalangan Ulama - Hisam Ahyani; Dian Permana; Agus Yosep Abduloh (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2020)
This research found that the Norma of Riba in Islamic Economics is a khilafiyah problem as well as the law of Bank Interest, in principle, mutual tolerance and mutual respect and respect for inter-opinions must be put forward. This is because each group of ulama has devoted their energy to seeking the law of the problem, and in the end their opinion remains different. Profit sharing norms in Islamic economics are an innovative step in an Islamic economy that is not only in accordance with people's behavior, but more than that profit sharing is a social balance step in obtaining economic opportunities. Thus, the profit sharing system can be seen as a more effective measure to prevent conflict between the rich and the poor from occurring in social life. The impact of Bank Interest (Riba) on the Country's Economy, among others, has an impact on several sectors including the Economic Impact. The higher the interest rate, the higher the price to be set on an item. Social Impact, the social impact of society related to Riba in terms of unfair income. Impact of Company Resilience, only companies that have resilience will survive